Prevalences and associated risk factors of HCV/HIV co-infection and HCV mono-infection among injecting drug users in a methadone maintenance treatment program in Taipei, Taiwan - Yen Yung-Feng; Yen Muh-Yong; Su Lien-Wen; Li Lan-Huei; Chuang Peing; Jiang Xiao-Ru; Deng Chung-Yeh (BMC, 2012)
Abstract Background Injecting drug users (IDUs) in Taiwan contributed significantly to an HIV/AIDS epidemic in 2005. In addition, studies that identified risk factors of HCV/HIV co-infection among IDUs were sparse. This study aimed to identify risk factors of HCV/HIV co-infection and HCV mono-infection, as compared with seronegativity, among injecting drug users (IDUs) at a large methadone maintenance treatment program (MMTP) in Taipei, Taiwan. Methods Data from enrollment interviews and HCV and HIV testing completed by IDUs upon admission to the Taipei City Hospital MMTP from 2006-2010 were included in this cross-sectional analysis. HCV and HIV testing was repeated among re-enrollees whose HCV or HIV test results were negative at the preceding enrollment. Backward stepwise multinomial logistic regression was used to identify risk factors associated with HCV/HIV co-infection and HCV mono-infection. Results Of the 1,447 IDUs enrolled, the prevalences of HCV/HIV co-infection, HCV mono-infection, and HIV mono-infection were 13.1%, 78.0%, and 0.4%, respectively. In backward stepwise multinomial regression analysis, after controlling for potential confounders, syringe sharing in the 6 months before MMTP enrollment was significantly positively associated with HCV/HIV co-infection (adjusted odds ratio [AOR]=27.72, 95% confidence interval [CI] 13.30-57.76). Incarceration was also significantly positively associated with HCV/HIV co-infection (AOR=2.01, 95% CI 1.71-2.37) and HCV mono-infection (AOR=1.77, 95% CI 1.52-2.06), whereas smoking amphetamine in the 6 months before MMTP enrollment was significantly inversely associated with HCV/HIV co-infection (AOR=0.44, 95% CI 0.25-0.76) and HCV mono-infection (AOR=0.49, 95% CI 0.32-0.75). HCV seroincidence was 45.25/100 person-years at risk (PYAR; 95% CI 24.74-75.92/100 PYAR) and HIV seroincidence was 0.53/100 PYAR (95% CI 0.06-1.91/100 PYAR) among re-enrolled IDUs who were HCV- or HIV-negative at the preceding enrollment. Conclusions IDUs enrolled in Taipei MMTPs had very high prevalences of HCV/HIV co-infection and HCV mono-infection. Interventions such as expansion of syringe exchange programs and education regarding HCV/HIV prevention should be implemented for this high-risk group of drug users.